Analysis Of The Impact Of Changes In The Negative Investment List On The Film Industry In Indonesia - Hendri (Faculty of Law, University of Mataram, 2024)
This study aims first to understand the implementation of Presidential Regulation Number 44 of 2016 for the film industry in Indonesia and, secondly, to identify and assess the impact of changes in the negative investment list on the film industry in Indonesia. The study utilizes a normative juridical research methodology, combining legal and conceptual approaches. The findings indicate that enforcement of Presidential Regulation Number 44 of 2016 in the Indonesian film industry resulted in the absence of international film companies operating in Indonesia before the regulation was implemented. However, this situation changed after films were removed from the Negative Investment List (DNI) as stipulated in Presidential Regulation Number 44 of 2016, an amendment to Presidential Regulation Number 39 of 2014 regarding categorizing closed and open business sectors with investment requirements. Modifying the negative investment list for the film industry in Indonesia has both positive and negative consequences. On the positive side, it has increased foreign investment, contributing to economic growth. Conversely, local investors need help competing with foreign investors due to financial resource disparities. The implementation of Presidential Regulation No. 44 of 2016 has had a significant impact on the investment landscape. Specifically, there has been an increase in foreign capital investment. However, it is worth noting that the number of Foreign Direct Investment (FDI) projects exceeds that of Domestic Direct Investment (DDI) projects. This difference can be attributed to the inability of domestic investors to compete effectively in the market.